Evaluation of Hepatoprotective Potential of Stem Bark of Neolamarckia cadamba against Chloroform and Over dose of Iron Dextran Induced Hepatotoxicity in Experimental Swiss Albino Mice - Das, Saumya; Shakya, Richa; Mazumder, Avijit; Bhati, Komal; Das, Manas Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: In general, use of herbal medicines are considered as the backbone in traditional system of medicines as it has been used for food, flavoring agents and in the form of medicines. Keeping in knowledge the increasing demand of herbal drugs over their synthetic counter parts and to restrain the worldwide problem of multidrug resistance (MDR) in hepatoprotective activity. Neolamarckia cadamba that is commonly called Cadamb is a standout amongst the most significant therapeutic plants having a place with the Rubiaceae family. It is one of such Ayurvedic cure that has been referenced in numerous Indian restorative written works. The arrangement of work includes gathering and confirmation of stem bark of cadamb plant pursued by shade drying, granulating, and extraction by two-fold cool maceration, phytochemical examination lastly screening of pharmacological exercises as expressed. Aim: The present study was carried out to establish hepatoprotective activity of hydro alcoholic extract of stem bark of Neolamarckia cadamba by using two established hepatotoxic screening models in Swiss albino mice (chloroform induced hepatotoxicity and iron over dose induced hepatotoxicity). Materials and Methods: The hepatoprotective activity of Neolamarckia cadamba was screened by hydro alcoholic extract of stem bark of Neolamarckia cadamba (NCHAE). The experimental animals were treated with corn oil and chloroform for a period of 7 days at a dose of 0.75mg/kg body weight, p.o to induce hepatotoxicity. In the second experimental model over dose of iron dextran induced hepatic damage was performed by administering 100 mg/kg, i.p.upto7 days, 3 consecutive periods. Blood samples were collected for the estimation of biochemical parameters and histopathological changes in liver was also performed. Silymarin (50 mg/kg; body weight) was used as standard referral of hepatoprotective agent. Results: Chloroform and iron over dose treatment were induced higher levels of liver marker enzymes and showed damage of hepatocytes. In histopathological findings there were significant opposed treatment with Neolamarckia cadamba dose dependently. The results indicated that biochemical changes produced by both the hepatotoxicity models were restored to normal by NCHAE. In the present study, the results of NCHAE was found significant hepatoprotective effect (***p<0.01) against both the inducing agents, which was indicated by the enhancement in biochemical parameters. Conclusion: The current study confirmed the hepatoprotective effect of NCHAE against the chloroform induced hepatotoxicity and iron over dose induced hepatotoxicity models and the activity is likely related to its potent antioxidant and ironchelating property. NCHAE therefore needs to be for further in-deep studies to correlate its bioactive constituents responsible for the pharmacological activity selected.
Keywords: Hepatoprotective; Neolamarckia cadamba; Chloroform; Iron dextran; Hepatotoxicity